2016
DOI: 10.3390/jfmk1040373
|View full text |Cite
|
Sign up to set email alerts
|

Could Cupping Therapy Be Used to Improve Sports Performance?

Abstract: "Cupping Therapy" is the topic chosen for the fourth editorial of this newly launched journal. The aim of this editorial is to deepen this interesting topic, little analyzed in the present literature, in order to explain the technique and deal with the evidence of the effects of cupping therapy in musculoskeletal disorders, and some possible relation to sports performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Studies regarding cupping therapy in sports medicine are insufficient, but the use of cupping has increased recently in elite athletes worldwide. [14]. The study showed that cupping was the second most used and satisfactory treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Studies regarding cupping therapy in sports medicine are insufficient, but the use of cupping has increased recently in elite athletes worldwide. [14]. The study showed that cupping was the second most used and satisfactory treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical outcome for PFJ OA should be improved, increasing the study on conventional pharmacological and/or non-pharmacological treatment strategies oriented to the exclusive biomechanical functions of the PFJ and the specific impairments linked with disease in this compartment. Kinesio tape, bracing, cupping therapy, adapted physical activity, kinesiotherapy and physiotherapy are interventions that all offer possibilities in the improvement of symptoms and/or reduction of PFJ stress and pain in patients with PFJ OA [27][28][29]. There are few studies in literature that demonstrate these important differences in knee joint compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Buna karşın 21 sporcuda tek doz yapılan hareketli kupa uygulamasının kalça ve diz ROM'unda artış yaparken, izokinetik diz fleksiyon kuvvetinde artış yapmadığı belirtilmiştir (34). Kupa uygulamasının kas-eklem ağrısı ve enflamasyonda azalma sonucunda performans artışı yaptığı ileri sürülmektedir (35).…”
Section: Performansunclassified